The American Rescue Plan Act Funds and Students With Extensive Support Needs: Three Considerations for Technology Access and Use. Issue 3 (August 2022) - Reed, Alexandra S.; Francis, Grace L.; Kinas-Jerome, Marci
The COVID-19 pandemic highlighted inequities in technology literacy and access for students with extensive support needs (ESN) in k-12 settings. Technology is critical for students with ESN to continue lifelong learning after graduation. The unprecedented level of funds from the American Relief Plan provides schools opportunities to invest in sustainable and accessible technology which benefits all students. The Universal Design for Learning (UDL) framework is used to increase access to learning for all students, and should be applied to decision making surrounding technology investment and purchasing. This essay provides three considerations for schools to reflect on when spending ARP Act funds: (a) use UD to purchase technology, (b) provide UDL professional development to teach technology literacy skills, and (c) provide learning opportunities aimed at technology use among students with ESN.